The Association between icaA and icaB Genes, Antibiotic Resistance and Biofilm Formation in Clinical Isolates of Staphylococci spp. - Seham Abdel-Shafi; Heba El-Serwy; Yehia El-Zawahry; Maysaa Zaki; Basel Sitohy; Mahmoud Sitohy (MDPI AG, 2022)
Sixty-six (66) Staphylococcus bacterial isolates were withdrawn from separate clinical samples of hospitalized patients with various clinical infections. Conventional bacteriological tests identified the species of all isolates, and standard microbiological techniques differentiated them into CoPS or CoNS. Their biofilm development was followed by an analysis via the MTP (microtiter tissue culture plates) technique, and we then investigated the presence/absence of icaA and icaB, which were qualified in the top-30 potent biofilm-forming isolates. Thirteen isolates (46.7%) showed the presence of one gene, six (20%) isolates exhibited the two genes, while ten (33.3%) had neither of them. The formation of staphylococci biofilms in the absence of ica genes may be related to the presence of other biofilm formation ica-independent mechanisms. CoPS was the most abundant species among the total population. S. aureus was the sole representative of CoPS, while S. epidermidis was the most abundant form of CoNS. Antibiotic resistance was developing against the most frequently used antimicrobial drugs, while vancomycin was the least-resisted drug. The totality of the strong and medium-strength film-forming isolates represented the majority proportion (80%) of the total investigated clinical samples. The biochemical pattern CoPS is associated with antibiotic resistance and biofilm formation and can be an alarming indicator of potential antibiotic resistance.